Mixed silver powder, its manufacturing method, and metal paste for joining

JP7651672B1Active Publication Date: 2025-03-26DOWA ELECTRONICS MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023218544
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-12-25
Publication Date
2025-03-26
Estimated Expiration
2043-12-25

AI Technical Summary

Benefits of technology

【0018】 本発明によれば、金属接合層に高い熱伝導率を付与可能な混合銀粉及びその製造方法、並びにこの混合銀粉を含む接合用金属ペーストを提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007651672000004
    Figure 0007651672000004
  • Figure 0007651672000005
    Figure 0007651672000005
  • Figure 0007651672000006
    Figure 0007651672000006
Patent Text Reader

Abstract

To provide a mixed silver powder capable of imparting high thermal conductivity to a metal bonding layer. The present invention relates to a particle size distribution obtained by wet measurement using a laser diffraction particle size distribution analyzer, in which the vertical axis indicates the volume distribution ratio and the horizontal axis indicates the particle diameter, The volume distribution ratio includes a first peak and a second peak, and is 1% or more; The particle diameter d of the first peak M1 and the particle diameter d of the second peak M2 The relationship is represented by the following formula (I) and formula (II): d M1 <d M2 (I) 4.5μm≦d M2 -d M1 ≦16.0μm (II) Fulfilling The relationship between a volume distribution ratio A of a peak having a smaller volume distribution ratio among the first peak and the second peak and a volume distribution ratio B at which the volume distribution ratio between the first peak and the second peak is minimum is expressed by the following formula (III) or formula (IV): 1.2≦A / B (III) 0 = B / A (IV) It is a mixed silver powder that satisfies the above requirements.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a mixed silver powder, a method for producing the same, and a metal paste for bonding. [Background technology]

[0002] Conventionally, solder has been used as a joining material for joining components. However, because the melting point of solder is low, it is difficult to use it for power device elements such as silicon carbide and gallium nitride, which have high operating temperatures. Therefore, metal pastes containing highly heat-resistant metal nanoparticles are currently used as joining materials.

[0003] For example, Patent Document 1 discloses a metal paste for joining that contains, as a paste component, a powder of metal nanoparticles such as silver nanoparticles having an agglomerated particle size of 1 μm or more; when this metal paste for joining is used to join two components, a joint with high joining strength can be obtained. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2014-224296 A Summary of the Invention [Problem to be solved by the invention]

[0005] Here, in bonding using a bonding metal paste, a metal bonding layer having high thermal conductivity is desired from the viewpoint of heat dissipation in the metal bonding layer.

[0006] Therefore, an object of the present invention is to provide a mixed silver powder capable of imparting high thermal conductivity to a metal bonding layer, a method for producing the same, and a bonding metal paste containing the mixed silver powder. [Means for solving the problem]

[0007] As a result of extensive research by the inventors to solve the above-mentioned problems, the inventors have completed the present invention described below.

[0008] That is, the gist of the present invention for solving the above-mentioned problems is as follows.

[0009] [1] In the particle size distribution measured in a wet state using a laser diffraction particle size distribution analyzer, the vertical axis is the volume distribution ratio and the horizontal axis is the particle size. The volume distribution ratio includes a first peak and a second peak, and is 1% or more; The particle diameter d of the first peak M1 and the particle diameter d of the second peak M2 The relationship is represented by the following formula (I) and formula (II): d M1 <d M2 (I) 4.5μm≦d M2 -d M1 ≦16.0μm (II) Fulfilling The relationship between a volume distribution ratio A of a peak having a smaller volume distribution ratio among the first peak and the second peak and a volume distribution ratio B at which the volume distribution ratio between the first peak and the second peak is minimum is expressed by the following formula (III) or formula (IV): 2≦A / B (III) 0 = B / A (IV) Meet the mixed silver powder.

[0010] [2] The mixed silver powder according to [1], wherein more than 50% of the volume distribution ratio of the first peak is derived from spherical silver powder, and more than 50% of the volume distribution ratio of the second peak is derived from flaky silver powder.

[0011] [3] The above d M1 is 0.5 μm or more and 1.5 μm or less, The above d M2 The mixed silver powder according to [1] or [2], wherein the average particle size is 5.0 μm or more and 17.5 μm or less.

[0012] [4] The mixed silver powder according to any one of [1] to [3], having a ratio of ignition loss to BET specific surface area of ​​0.65 or less.

[0013] [5] Tap density is 3.5g / cm 3 The mixed silver powder according to any one of [1] to [4] above.

[0014] [6] A method for producing a mixed silver powder, comprising a mixing step of mixing a first silver powder and a second silver powder, The first silver powder and the second silver powder are each measured in a wet state using a laser diffraction particle size distribution analyzer, and the particle size distribution is shown on the vertical axis as a volume distribution ratio and on the horizontal axis as a particle size distribution. The particle diameter d of the peak of the volume distribution ratio of the first silver powder is maximum S1 and the particle diameter d of the peak of the maximum volume distribution ratio of the second silver powder. S2 The relationship is expressed by the following formula (i) and formula (ii): d S1 <d S2 (i) 4.6μm≦d S2 -d S1 ≦16.0μm (ii) Fulfilling The cumulative 94% diameter D of the first silver powder 94 and the cumulative 6% diameter D6 of the second silver powder is expressed by the following formula (iii): D 94 ≦D6 (iii) A method for producing mixed silver powder that satisfies the above requirements.

[0015] [7] The method for producing a mixed silver powder described in [6], wherein the first silver powder is a spherical silver powder and the second silver powder is a flake silver powder.

[0016] [8] The spherical silver powder has a cumulative 50% diameter D 50 is 0.5 μm or more and 1.5 μm or less, and the tap density is 2.0 g / cm 3 and the BET specific surface area is 0.6m 2 / g or more 2.2m 2 / g or less, The flake silver powder has a cumulative 50% diameter D 50 is 5.0 μm or more and 17.5 μm or less, and the tap density is 2.0 g / cm 3 and the BET specific surface area is 0.2 m 2 / g or more 2.0m 2 / g or less and an aspect ratio of 3 or more.

[0017] [9] A metal paste for joining, comprising the mixed silver powder according to any one of [1] to [5]. Effect of the Invention

[0018] According to the present invention, it is possible to provide a mixed silver powder capable of imparting high thermal conductivity to a metal bonding layer, a method for producing the same, and a bonding metal paste containing the mixed silver powder. [Brief description of the drawings]

[0019] [Figure 1] FIG. 4 is a schematic diagram illustrating a method for evaluating shear strength in the examples. [Diagram 2] 2 is a graph showing the particle size distribution of the silver powder of Example 1. [Diagram 3] 4 is a graph showing the particle size distribution of the silver powder of Example 2. [Figure 4] 4 is a graph showing the particle size distribution of the silver powder of Example 3. [Diagram 5] 1 is a graph showing the particle size distribution of the silver powder of Example 4. [Figure 6] 1 is a graph showing the particle size distribution of the silver powder of Example 5. [Figure 7] This is an SEM photograph (2000x) of flake silver powder A. [Figure 8] This is an SEM photograph (2000x) of flake silver powder B. [Figure 9] This is an SEM photograph (2000x) of flake silver powder C. [Figure 10] This is an SEM photograph (2000x) of flake silver powder D. [Figure 11]This is an SEM photograph (2000x) of flake silver powder E. [Figure 12] This is an SEM photograph (2000x magnification) of spherical silver powder A. [Figure 13] This is an SEM photograph (20,000x) of spherical silver powder A. [Figure 14] This is an SEM photograph (2000x) of spherical silver powder B. [Figure 15] 1 is an SEM photograph (2000x) of the silver powder of Example 1. [Figure 16] 1 is an SEM photograph (2000x) of the silver powder of Example 2. [Figure 17] 1 is an SEM photograph (2000x) of the silver powder of Example 3. [Figure 18] 1 is an SEM photograph (2000x) of the silver powder of Example 4. [Figure 19] 1 is an SEM photograph (2000x) of the silver powder of Example 5. [Figure 20] 1 is an SEM photograph (2000x) of the silver powder of Comparative Example 4. [Figure 21] 1 is an SEM photograph (2000x) of the silver powder of Comparative Example 5. [Figure 22] 1 is an SEM photograph (2000x) of the silver powder of Comparative Example 6. [Figure 23] 1 is an SEM photograph (2000x) of the silver powder of Comparative Example 7. [Figure 24] 4 is a graph showing the particle size distribution of the silver powder according to Comparative Example 1. [Diagram 25] 4 is a graph showing the particle size distribution of the silver powder according to Comparative Example 2. [Figure 26] 1 is a graph showing the particle size distribution of silver powder according to Comparative Example 3. [Figure 27] 11 is a graph showing the particle size distribution of the silver powder according to Comparative Example 4. [Figure 28] 11 is a graph showing the particle size distribution of the silver powder according to Comparative Example 5. [Figure 29] 1 is a graph showing the particle size distribution of silver powder according to Comparative Example 6. [Diagram 30] 11 is a graph showing the particle size distribution of the silver powder according to Comparative Example 7. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] (Terminology and Measurement Methods) Prior to describing the embodiments, the terms and measurement methods used in this specification will be described.

[0021] <Particle size distribution measurement method> In this specification, the cumulative 6% particle size (D6) and cumulative 10% particle size (D 10 ), cumulative 50% particle diameter (D 50 ), cumulative 90% particle diameter (D 90 ), cumulative 94% particle diameter (D 94 ) and their distribution were measured by the following method. 0.1 g of silver powder was added to 40 mL of isopropyl alcohol (IPA) and dispersed for 2 minutes using an ultrasonic homogenizer (apparatus name: US-150T, manufactured by Nippon Seiki Seisakusho Co., Ltd.; 19.5 kHz, tip diameter 18 mm), and then measured in wet mode using a laser diffraction particle size distribution measuring device (Microtrac-Bell Co., Ltd., Microtrolac MT-3300 EXII). Note that for only the silver powder (spherical silver powder A) in Comparative Example 2 described later, 0.1 g of silver powder was added to 40 mL of a 1 wt% polyvinylpyrrolidone (PVP) solution (solvent is isopropyl alcohol), dispersed for 2 minutes using an ultrasonic homogenizer, and the resulting solution was used for measurement. In the present invention, the measurement was performed by the above method, and a graph of particle size distribution was obtained, in which the vertical axis is the volume distribution ratio (unit: %) and the horizontal axis is the particle size (unit: μm), calculated on a volume basis. The graph of particle size distribution is a histogram, and the volume distribution ratio is obtained by dividing the cumulative value of the particle volume in each particle size range by the total volume of the particles measured. Note that, for the particle size range on the horizontal axis, the ratio between the minimum particle size values ​​in adjacent ranges was measured to be 1.09. In this specification, the "peak" in the particle size distribution means the point where the particle diameter is smallest in the section where the volume frequency distribution ratio is maximum. In addition, when the peak is specified, if there are adjacent sections with the same volume distribution ratio, the section with the smaller particle diameter is used.

[0022] <Ignition loss of silver powder> The ignition loss of silver powder (Ig-loss) was determined by weighing 2 g of the silver powder sample (w1), placing it in a magnetic crucible, heating it strongly at 800 °C for 30 minutes, cooling it, and then weighing it (w2), using the formula "ignition loss (%) = [(w1 - w2) / w1] × 100".

[0023] <BET specific surface area> Using a specific surface area measuring device that employs the BET method (manufactured by MOUNTECH Co., Ltd., Macsorb HM-model 1210), 3 g of silver powder was placed in the measurement cell, and a carrier gas mixture of 70% by volume of He gas and 30% by volume of N2 gas was passed through the measurement cell for degassing at 60 °C for 10 minutes, and then it was determined by the BET one-point method.

[0024] <Tap density (TAP)> The tap density of silver powder is the apparent density of the silver powder in the container after a predetermined amount of silver powder is weighed and put into a container of a predetermined volume, and the operation of dropping the container at a predetermined drop height is performed a predetermined number of times (hereinafter referred to as after tapping), and it is obtained by dividing the weight of the silver powder in the container by the apparent volume of the silver powder in the container. Specifically, for the tap density of silver powder, a tap density measuring device (manufactured by Shibayama Kagaku Co., Ltd., bulk specific gravity measuring device SS-DA-2) was used. 30 g of silver powder was weighed and put into a container (20 mL test tube), and tapping was performed 1,000 times at a drop height of 20 mm. The tap density was obtained by dividing the weight of the silver powder, which is 30 g, by the apparent volume (mL) of the silver powder after tapping. For the flaky silver powder B and flaky silver powder C described later and the silver powder according to Comparative Examples 4 and 5, the weight of the silver powder to be weighed was 15 g, and the tap density was obtained by dividing the weight of the silver powder, which is 15 g, by the apparent volume (mL) of the silver powder after tapping.

[0025] <Average aspect ratio> Here, when using a uniform model of disk particles, the average aspect ratio can be calculated by "average aspect ratio = D 50 / t" (where t means thickness). Also, the thickness t (unit: μm) is "t = D 50 / ((ρ × (D 50 / 2) × BET specific surface area)-2) (ρ means the particle density). Therefore, in this specification, the average aspect ratio of silver powder is the D 50 , the BET specific surface area of ​​the silver powder, and ρ, the true density of the silver powder, 10.49 g / cm 3 Using the above, the average aspect ratio is calculated as (10.49 × (D 50 The calculation was made using the formula "Earnings Ratio (EBITDA) x BET (%) - 2".

[0026] <Spherical silver powder> In this specification, the term "spherical silver powder" refers to a shape close to a sphere and having an average aspect ratio of less than 2.

[0027] <Flake silver powder> In this specification, the term "flake-shaped silver powder" refers to silver powder having a shape including a flat plate, a thin rectangular parallelepiped, a thin flake, or a scale shape, and having an average aspect ratio of 2 or more.

[0028] (Mixed silver powder) The mixed silver powder of the present invention has a particle size distribution (hereinafter sometimes simply referred to as "particle size distribution") obtained by wet measurement using a laser diffraction particle size distribution analyzer, in which the vertical axis represents the volume distribution ratio and the horizontal axis represents the particle diameter, and includes a first peak and a second peak having a volume distribution ratio of 1% or more, and the particle diameter d M1 and the particle diameter of the second peak d M2 The relationship is represented by the following formula (I) and formula (II): d M1 <d M2 (I) 4.5μm≦d M2 -d M1 ≦16.0μm (II) It satisfies the following. Furthermore, the mixed silver powder of the present invention has a particle diameter d M2 and the particle diameter of the first peak d M1 Difference from (d M2 -d M1) is in the above range, and the two peaks are separated by the above range, so that at least one valley occurs between the first peak and the second peak in the particle size distribution of the mixed silver powder. In the mixed silver powder of the present invention, the relationship between the volume distribution ratio A of the peak having the smaller volume distribution ratio out of the first peak and the second peak, and the volume distribution ratio B of the position where the volume distribution ratio of the valley between the first peak and the second peak is minimum, is expressed by the following formula (III) or formula (IV): 1.2≦A / B (III) 0 = B / A (IV) It satisfies the following. The mixed silver powder as described above can impart high thermal conductivity to the metal bonding layer. The reason for this is presumably that the silver particles having a small particle size and high sinterability that form the first peak enter the gaps between the silver particles having a large particle size that form the second peak, and increase the conductive paths between the silver particles having a large particle size in the metal bonding layer, thereby obtaining the effect of reducing the number of particles obtained by using large silver particles and the effect of increasing the contact surface between the large silver particles. In addition, in the particle size distribution of the mixed silver powder, it is preferable that there are only two peaks with a volume distribution ratio of 1% or more, but if there are three or more peaks with a volume distribution ratio of 1% or more, the first peak and the second peak refer to the two peaks with the largest volume distribution ratios.

[0029] In the particle size distribution of the mixed silver powder, the particle diameter of the second peak d M2 and the particle diameter of the first peak d M1 Difference from (d M2 -d M1 ) is 4.5 μm or more, and preferably 6.0 μm or more, and is 16.0 μm or less, and preferably 13.0 μm or less.

[0030] In the mixed silver powder of the present invention, the relationship between the volume distribution ratio A and the volume distribution ratio B is not particularly limited as long as it satisfies formula (III) or formula (IV), but it is preferable that it satisfies formula (III). Here, in the particle size distribution of the mixed silver powder, the ratio (A / B) of the volume distribution ratio A to the volume distribution ratio B is 1.2 or more, and preferably 1.5 or more. On the other hand, the ratio (A / B) of the volume distribution ratio A to the volume distribution ratio B may be, for example, 1.5 or less, or 1.25 or less.

[0031] The volume distribution ratio A is not particularly limited as long as it satisfies the relationship of formula (III), but is preferably 1.0% or more, more preferably 1.6% or more, and is preferably 4.0% or less, more preferably 3.0% or less.

[0032] The volume distribution ratio B is not particularly limited as long as it satisfies the relationship of formula (III), but is preferably 0.5% or more, more preferably 0.7% or more, and is preferably 3.0% or less, more preferably 2.0% or less.

[0033] In the particle size distribution of the mixed silver powder, it is preferable that more than 50% of the volume distribution ratio of the first peak is derived from spherical silver powder, and more than 50% of the volume distribution ratio of the second peak is derived from flaky silver powder. If more than 50% of the volume distribution ratio of the first peak is derived from spherical silver powder and more than 50% of the volume distribution ratio of the second peak is derived from flaky silver powder, then fine spherical silver particles having a small particle size and high sinterability will easily penetrate into the gaps between larger flaky silver particles in the metal bonding layer, thereby increasing the conductive paths between larger flaky silver particles in the metal bonding layer, thereby achieving the effect of reducing the number of flaky silver powder particles and the effect of further increasing the contact area between flaky silver particles having flat surfaces. The volume distribution ratio of the first peak is preferably 70% or more, more preferably 90% or more, derived from the spherical silver powder.Furthermore, it is even more preferable that the volume distribution ratio of the first peak is 100% derived from the spherical silver powder, i.e., it is derived only from the spherical silver powder. The volume distribution ratio of the second peak is preferably 70% or more, more preferably 90% or more, derived from the flaky silver powder.Furthermore, it is even more preferable that the volume distribution ratio of the second peak is 100% derived from the flaky silver powder, i.e., it is derived only from the flaky silver powder.

[0034] In the particle size distribution of the mixed silver powder, d M1 is 0.5 μm or more and 1.5 μm or less, and d M2 It is preferable that the thickness is 5 μm or more and 17.5 μm or less. d M1 and d M2 Within the above range, it is possible to achieve both high sinterability due to the fine silver powder and the effect of reducing the number of particles due to the large silver powder and the effect of increasing the contact surface between the large silver particles. d M1 is preferably 0.6 μm or more, more preferably 0.8 μm or more, and is preferably 1.4 μm or less, more preferably 1.3 μm or less. d M2 is preferably 6.0 μm or more, more preferably 7.0 μm or more, and is preferably 16.0 μm or less, more preferably 11.0 μm or less.

[0035] Mixed silver powder D 10 is preferably 0.3 μm or more, more preferably 0.4 μm or more, and is preferably 1.5 μm or less, more preferably 1.2 μm or less. Mixed silver powder D 10 If the diameter is 0.3 μm or more, fine silver particles having a small particle size can densely fill the gaps between the large silver particles. On the other hand, if the D10 of the mixed silver powder is 1.5 μm or less, the good sinterability of small silver particles can be utilized.

[0036] Mixed silver powder D 50 is preferably 1.0 μm or more, more preferably 1.1 μm or more, and is preferably 8.0 μm or less, more preferably 6.0 μm or less.

[0037] Mixed silver powder D 90 is preferably 7.0 μm or more, more preferably 8.0 μm or more, and is preferably 20.0 μm or less, more preferably 17.0 μm or less. Mixed silver powder D 90 If the diameter is 7.0 μm or more, it is possible to reduce the number of large silver particles in the metal bonding layer and increase the contact area between the silver particles. On the other hand, the mixed silver powder D 90 If the diameter is 20.0 μm or less, the gaps between the large particles are not too wide, and the silver particles having a smaller particle size can be densely packed in.

[0038] In the mixed silver powder, (D 90 -D 10 ) / D 50 is preferably 1.8 or more, more preferably 1.9 or more, and is preferably 10.0 or less, more preferably 7.2 or less. Within the above range, a certain number of fine silver powder with small particle sizes and silver powder with large particle sizes are mixed together, and the silver particles with small particle sizes can densely fill the gaps between the larger particles, improving the filling property of the metal bonding layer.

[0039] The tap density of the mixed silver powder is 3.5g / cm 3 It is preferable that the content is 5.0 g / cm or more. 3 More preferably, it is 7.0 g / cm or more. 3 It is preferable that the content is 6.3 g / cm or less. 3 It is more preferable that: The tap density of the mixed silver powder is 3.5g / cm 3 If this is the case, the filling property of the metal bonding layer is improved. On the other hand, the tap density of the mixed silver powder is 7.0 g / cm 3 If the filling rate is more than this, the bonding material will become too hard and brittle, and there is a risk of cracks or the like occurring due to warping caused by thermal stress or the like.

[0040] The BET specific surface area of ​​the mixed silver powder is 0.61m 2 / g or more, and 0.65m 2 / g or more is more preferable, and 1.40m 2 / g or less, and 1.00m 2 It is more preferable that the molecular weight is not more than 1 / g. The BET specific surface area of ​​the mixed silver powder is 0.61m 2 / g or more, a sufficient contact area between particles can be ensured. On the other hand, the BET specific surface area of ​​the mixed silver powder is 1.40 m 2 If the viscosity of the paste for forming the metal bonding layer is less than or equal to 1 / g, the viscosity of the paste for forming the metal bonding layer can be maintained at a good level.

[0041] In the mixed silver powder, the ratio of ignition loss (Ig-loss) to BET specific surface area ("Ig-loss" / "BET specific surface area") is preferably 0.15 or more, more preferably 0.30 or more, and is preferably 0.65 or less, more preferably 0.57 or less. If the "Ig-loss" / "BET specific surface area" of the mixed silver powder is 0.15 or more, the silver powder can be dispersed well. On the other hand, if the "Ig-loss" / "BET specific surface area" of the mixed silver powder is 0.65 or less, the amount of impurities between the particles can be kept low, which reduces the resistance between the particles after heating and improves the thermal conductivity of the metal bonding layer. Here, the ratio of ignition loss (Ig-loss) to the BET specific surface area is the value of ignition loss (Ig-loss) in silver powder in units of mass%, expressed in units of m 2 / g, divided by the value of the BET specific surface area of ​​the silver powder. Note that, although the units of "Ig-loss" / "BET specific surface area" are omitted in this specification, the units are "mass% g / m 2 "

[0042] The mixed silver powder of the present invention is not particularly limited as long as it satisfies the relationships of formulas (I) to (IV), but it may be a mixture containing a first silver powder and a second silver powder described below in a predetermined ratio.

[0043] (Method of manufacturing mixed silver powder) The method for producing a mixed silver powder of the present invention (hereinafter, may be simply referred to as the "production method") includes a mixing step of mixing a first silver powder and a second silver powder, and a particle size distribution obtained by wet measuring the first silver powder and the second silver powder using a laser diffraction particle size distribution measuring device, the particle size distribution being the volume distribution ratio on the vertical axis and the particle diameter on the horizontal axis, and the particle diameter d of the peak of the volume distribution ratio at which the first silver powder has a maximum is obtained. S1 and the particle diameter d of the peak of the maximum volume distribution ratio of the second silver powder S2 The relationship is expressed by the following formula (i) and formula (ii): d S1 <d S2 (i) 4.6μm≦d S2 -d S1 ≦16.0μm (ii) Fulfilling Cumulative 94% diameter of the first silver powder D 94 and the cumulative 6% diameter D6 of the second silver powder are expressed by the following formula (iii): First Silver Powder D 94 ≦D6 of silicic acid powder (iii) This is a way to satisfy the above. With the above-mentioned mixed silver powder, it is possible to obtain a mixed silver powder capable of imparting high thermal conductivity to the metal bonding layer. The mixed silver powder of the present invention described above can be obtained by the manufacturing method of the present invention. In the mixing step of the manufacturing method of the present invention, the means for mixing the first silver powder and the second silver powder is not particularly limited, and can be, for example, a stirrer such as a Henschel mixer or a sample mill.

[0044] In the particle size distribution of the first silver powder and the second silver powder, the particle diameter d of the peak of the volume distribution ratio at which the second silver powder is maximum S2 and the particle diameter d of the peak of the maximum volume distribution ratio of the first silver powder. S1 Difference from (d S2 -d S1 ) is 4.6 μm or more, and preferably 6.0 μm or more, and is 16 μm or less, and preferably 12.0 μm or less.

[0045] In the particle size distribution of the first silver powder and the second silver powder, the cumulative 6% diameter D6 of the second silver powder and the cumulative 94% diameter D of the first silver powder are 94 Difference between (D6-D 94 ) is preferably 0.0 μm or more, more preferably 0.1 μm or more, and is preferably 3.0 μm or less, more preferably 2.5 μm or less.

[0046] The mass ratio of the first silver powder to the total mass of the first silver powder and the second silver powder is preferably 10% by mass or more, more preferably 20% by mass or more, and is preferably 90% by mass or less, and more preferably 80% by mass or less. If the mass ratio of the first silver powder to the total mass of the first silver powder and the second silver powder is within the above range, a certain number of small-particle fine silver powder and large flake silver powder are mixed together, and the small-particle silver particles can densely penetrate into the gaps between the larger particles, improving the filling property of the metal bonding layer and allowing the effects of each silver powder to be exerted.

[0047] In the particle size distribution of the first silver powder, d S1 is preferably 0.4 μm or more, more preferably 0.7 μm or more, and is preferably 1.5 μm or less, more preferably 1.3 μm or less.

[0048] In the particle size distribution of the first silver powder, the peak volume distribution ratio of the maximum volume distribution ratio of the first silver powder is preferably 4.0% or more, more preferably 5.0% or more, and there is no particular upper limit.

[0049] The shape of the first silver powder is not particularly limited, but it is preferably spherical, that is, the first silver powder is preferably spherical silver powder.

[0050] First Silver Powder D 10is preferably 0.1 μm or more, more preferably 0.2 μm or more, and is preferably 0.7 μm or less, more preferably 0.4 μm or less.

[0051] First Silver Powder D 50 is preferably 0.5 μm or more, more preferably 0.6 μm or more, and is preferably 1.5 μm or less, more preferably 1.2 μm or less.

[0052] First Silver Powder D 90 is preferably 0.8 μm or more, more preferably 1.2 μm or more, and is preferably 1.9 μm or less, more preferably 1.6 μm or less.

[0053] First Silver Powder D 94 is preferably 0.9 μm or more, more preferably 1.3 μm or more, and is preferably 2.0 μm or less, more preferably 1.8 μm or less. When the D10, D50, D90, and D94 values ​​of the first silver powder are within the above ranges, the sinterability is not deteriorated and the first silver powder can densely penetrate into the gaps between large particles.

[0054] The tap density of the first silver powder is 2.0 g / cm 3 It is preferable that the content is 3.5 g / cm or more. 3 More preferably, it is 7.0 g / cm or more. 3 It is preferable that the content is 6.0 g / cm or less. 3 It is more preferable that: The tap density of the first silver powder is 2.0 g / cm 3 If the amount is more than this, the filling property of the metal bonding layer can be improved. On the other hand, the tap density of the first silver powder is 7.0 g / cm 3 If the filling rate is more than this, the bonding material will become too hard and brittle, and there is a risk of cracks or the like occurring due to warping caused by thermal stress or the like.

[0055] The BET specific surface area of ​​the first silver powder is 0.6m 2 / g or more, and 0.8m 2 / g or more is more preferable, and 2.2m 2 / g or less, and 1.8m 2 It is more preferable that the molecular weight is not more than 1 / g. BET specific surface area is 0.6m 2 If it is 0.1 to 1.0 μm / g or more, the sinterability can be improved. On the other hand, the BET specific surface area is 2.2m 2 / g or less, the viscosity of the paste for forming the metal bonding layer containing the mixed silver powder can be maintained at a good level.

[0056] In the first silver powder, the ratio of ignition loss (Ig-loss) to BET specific surface area ("Ig-loss" / "BET specific surface area") is preferably 0.15 or more, more preferably 0.20 or more, and is preferably 0.65 or less, more preferably 0.57 or less. If the "Ig-loss" / "BET specific surface area" of the first silver powder is 0.15 or more, the dispersibility of the silver powder can be improved. On the other hand, if the "Ig-loss" / "BET specific surface area" of the first silver powder is 0.65 or less, impurities between particles can be kept to a minimum, which reduces the resistance between particles after heating and improves the thermal conductivity of the metal bonding layer.

[0057] In the particle size distribution of the second silver powder, d S2 is preferably 5.0 μm or more, more preferably 7.0 μm or more, and is preferably 17.5 μm or less, more preferably 16.0 μm or less.

[0058] In the particle size distribution of the second silver powder, the peak volume distribution ratio of the maximum volume distribution ratio of the second silver powder is preferably 4.0% or more, more preferably 5.0% or more, and there is no particular upper limit.

[0059] The shape of the second silver powder is not particularly limited, but it is preferably in the form of flakes, that is, the first silver powder is preferably in the form of flakes. Here, when the second silver powder is a flaky silver powder, the aspect ratio of the flaky silver powder is preferably 3 or more, more preferably 8 or more, and is preferably 40 or less, more preferably 30 or less. If the aspect ratio of the flake silver powder is 3 or more, there will be a sufficient amount of flat surface area on each silver particle, ensuring a sufficient contact area between the particles. On the other hand, if the aspect ratio of the flaky silver powder is 40 or less, good filling properties of the metal bonding layer can be ensured.

[0060] The D6 of the second silver powder is preferably 1.0 μm or more, more preferably 1.4 μm or more, and is preferably 5.0 μm or less, more preferably 4.0 μm or less.

[0061] Second Silver Powder D 10 is preferably 1.5 μm or more, more preferably 2.0 μm or more, and is preferably 7.0 μm or less, more preferably 5.0 μm or less.

[0062] Second Silver Powder D 50 is preferably 5.0 μm or more, more preferably 6.0 μm or more, and is preferably 17.5 μm or less, more preferably 13.0 μm or less.

[0063] Second Silver Powder D 90 is preferably 8.0 μm or more, more preferably 12.0 μm or more, and is preferably 25.0 μm or less, more preferably 22.0 μm or less. Second silver powder D6, D 10 , D 50 , D 90If the amount of silver powder that is not flaked is within the above range, the amount of silver powder that is not flaked and the amount of particles that are excessively flaked are small, so that the mixture is compatible with the first silver powder and the filling property of the metal bonding layer can be improved.

[0064] The tap density of the second silver powder is 2.0 g / cm 3 It is preferable that the content is 4.0 g / cm or more. 3 More preferably, it is 7.0 g / cm or more. 3 It is preferable that the density is 6.5 g / cm or less. 3 It is more preferable that: The tap density of the second silver powder is 2.0 g / cm 3 If the amount is equal to or greater than this, there will be few excessively flaked particles, and the filling property of the metal bonding layer can be improved. On the other hand, the tap density of the second silver powder is 7.0 g / cm 3 If the particle size is less than this, there will be a sufficient amount of flat surfaces on the particles to ensure a sufficient contact area between the particles.

[0065] The BET specific surface area of ​​the second silver powder is 0.2 m 2 / g or more, and 0.25m 2 / g or more is more preferable, and 2.0m 2 / g or less, and 1.2m 2 It is more preferable that the molecular weight is not more than 1 / g. BET specific surface area is 0.2m 2 / g or more, there are sufficient flat surfaces of the particles to ensure the contact area. On the other hand, the BET specific surface area is 2.0m 2 If the particle size is less than 1 / g, there are few excessively flaked particles or fine particles, and the effect of large flake silver powder can be improved.

[0066] In the second silver powder, the ratio of ignition loss (Ig-loss) to BET specific surface area ("Ig-loss" / "BET specific surface area") is preferably 0.15 or more, more preferably 0.20 or more, and is preferably 0.65 or less, more preferably 0.57 or less. If the "Ig-loss" / "BET specific surface area" of the second silver powder is 0.15 or more, the dispersibility of the silver powder can be improved. On the other hand, if the "Ig-loss" / "BET specific surface area" of the second silver powder is 0.65 or less, impurities between particles can be kept to a minimum, which reduces the resistance between particles after heating and improves the thermal conductivity of the metal bonding layer.

[0067] In one embodiment, the first silver powder is preferably a spherical silver powder, and the second silver powder is preferably a flake silver powder. If the first silver powder is spherical silver powder and the second silver powder is flaky silver powder, the small spherical silver powder can be densely packed between the larger flaky silver particles, thereby increasing the conductive paths between the large flaky silver particles in the metal bonding layer, thereby achieving the effect of reducing the number of flaky silver powder particles and the effect of increasing the contact area between flaky silver particles having flat surfaces.

[0068] In one embodiment, when the first silver powder is a spherical silver powder and the second silver powder is a flake silver powder, the spherical silver powder has a cumulative 50% diameter D 50 is 0.5 μm or more and 1.5 μm or less, and the tap density is 2.0 g / cm 3 and the BET specific surface area is 0.6m 2 / g or more 2.2m 2 / g or less, and the flaky silver powder has a cumulative 50% diameter D 50 is 5 μm or more and 16 μm or less, and the tap density is 2.0 g / cm 3 and the BET specific surface area is 0.2 m 2 / g or more 2.0m 2 / g or less and an aspect ratio of 3 or more is preferred. If the spherical silver powder and flaky silver powder have the above-mentioned properties, the fine spherical silver particles with small particle size and high sinterability will easily penetrate into the gaps between the larger flaky silver particles in the metal bonding layer, thereby increasing the conductive paths between the larger flaky silver particles, thereby achieving the effect of reducing the particle number of the flaky silver powder and the effect of increasing the contact area between the flaky silver particles having flat surfaces.

[0069] The first silver powder and the second silver powder are not particularly limited and can be produced by a conventional method.

[0070] (Metal paste for bonding) The bonding metal paste of the present invention contains the above-mentioned mixed silver powder of the present invention. Since the bonding metal paste of the present invention contains the mixed silver powder of the present invention, it can impart high thermal conductivity to the metal bonding layer. The bonding metal paste usually contains a solvent, which is not particularly limited and may be, for example, water, monoalcohol, polyol, ether compound, glycol ether acetate, nitrogen-containing cyclic compound, ester compound, or the like. Examples of monoalcohols include 1-octanol, terpineol, texanol, phenoxypropanol, 1-decanol, 1-dodecanol, 1-tetradecanol, Tersolve MTPH (manufactured by Nippon Terpene Chemical Co., Ltd.), dihydroterpinyloxyethanol (manufactured by Nippon Terpene Chemical Co., Ltd.), Tersolve TOE-100 (manufactured by Nippon Terpene Chemical Co., Ltd.), and Tersolve DTO-210 (manufactured by Nippon Terpene Chemical Co., Ltd.). Examples of polyols include 3-methyl-1,3-butanediol, 2-ethyl-1,3-hexanediol (octanediol), hexyl diglycol, 2-ethylhexyl glycol, dibutyl diglycol, glycerin, dihydroxyterpineol, 3-methylbutane-1,2,3-triol (isoprene triol A (IPTL-A), manufactured by Nippon Terpene Chemical Co., Ltd.), and 2-methylbutane-1,2,4-triol (isoprene triol B (IPTL-B), manufactured by Nippon Terpene Chemical Co., Ltd.). Examples of the ether compound include butyl carbitol, diethylene glycol monobutyl ether, terpinyl methyl ether (manufactured by Nippon Terpene Chemical Co., Ltd.), and dihydroterpinyl methyl ether (manufactured by Nippon Terpene Chemical Co., Ltd.). Examples of glycol ether acetates include butyl carbitol acetate, diethylene glycol monobutyl ether acetate, ethylene glycol monomethyl ether acetate, ethylene glycol monoethyl ether acetate, and diethylene glycol monoethyl ether acetate. Examples of the nitrogen-containing cyclic compound include 1-methylpyrrolidinone and pyridine. Examples of ester compounds include γ-butyrolactone, methoxybutyl acetate, methoxypropyl acetate, ethyl lactate, 3-hydroxy-3-methylbutyl acetate, dihydroterpinyl acetate, Tersolve IPG-2Ac (manufactured by Nippon Terpene Chemical Co., Ltd.), Tersolve THA-90 (manufactured by Nippon Terpene Chemical Co., Ltd.), and Tersolve THA-70 (manufactured by Nippon Terpene Chemical Co., Ltd.). The above-listed solvents may be used alone or in combination of two or more. EXAMPLES

[0071] The present invention will be described in more detail below using examples, but the present invention is not limited to the following examples in any way. The BET specific surface area, particle size distribution, ignition loss (Ig-loss), tap density, and average aspect ratio were measured or calculated by the methods described above.

[0072] (Preparation of flake silver powder A) First, 167.1 kg of 26 wt% aqueous ammonia solution was added to 2922 kg of an aqueous silver nitrate solution containing 68.8 kg of silver as an aqueous silver ion solution to generate an aqueous silver ammine complex solution. Furthermore, 266 kg of an aqueous 6 wt% aqueous hydrazine solution was added as a reducing agent to this aqueous silver ammine complex solution to obtain a first liquid. The rate of addition of the reducing agent was 80 L / min. The first liquid was in the form of a slurry containing silver particles. The first liquid was filtered, washed with water, and then dried to obtain a pre-silver powder. This pre-silver powder is composed of uniform silver particles in an agglomerated state. 15.5 kg of the above pre-silver powder was put into a Henschel type mixer (Mitsui Mining Co., Ltd., FM mixer, model FM75, using SO type stirring blade) and stirred at 900 rpm for 1 minute, after which 49.6 g of palmitic acid (0.32 wt% based on the weight of the pre-silver powder (calculated as 49.6 g palmitic acid / 15500 g pre-silver powder x 100)) was added as a lubricant and mixed and stirred at a stirring blade speed of 2600 rpm for 20 minutes (lubricant mixing process). This process was carried out in multiple batches to obtain lubricant-treated silver powder in which the lubricant was dispersed on the surfaces of the silver particles. 31 kg of the obtained lubricant-treated silver powder was placed in a rolling ball mill with an inner diameter of 60 cm and a length of 40 cm together with 313.2 kg of SUS balls (diameter 1.6 mm), and flaking treatment was carried out under the conditions of a rotation speed of 21 rpm and a treatment time of 7 hours. After the treatment, the balls and the flaked silver powder were separated using a vibrating sieve. 30 kg of the flaked silver powder was added to about 35 L of neoethanol adjusted to 28°C or higher, stirred for 30 minutes, and then separated into solid and liquid using a pressure filter, followed by drying. 14 kg of the dried flaked silver powder was added to a Henschel type mixer (Mitsui Mining Co., Ltd., FM mixer, model FM75, using SO type stirring blades), stirred for 1 minute at 900 rpm, and then crushed for 15 minutes at 2600 rpm. In addition, in order to remove coarse particles from the crushed silver powder, it was sieved using a dry sieve device (Freund Turbo Co., Ltd., TS125×200 type / 24 μm mesh screen) to obtain flaked silver powder A. Table 1 shows the various measurement results of flaked silver powder A. Figure 7 shows an SEM photograph (2000x) of flaked silver powder A.

[0073] (Preparation of flake silver powder B) FA-S-10 manufactured by DOWA Electronics was prepared as flake silver powder B. Various measurement results of flake silver powder B are shown in Table 1. Also, Figure 8 shows an SEM photograph (2000x) of flake silver powder B.

[0074] (Preparation of flake silver powder C) FA-S-18 manufactured by DOWA Electronics was prepared as flake silver powder C. Table 1 shows the various measurement results of flake silver powder C. Figure 9 shows an SEM photograph (2000x) of flake silver powder C.

[0075] (Preparation of flake silver powder D) First, 167.1 kg of 26 wt% aqueous ammonia solution was added to 2922 kg of an aqueous silver nitrate solution containing 68.8 kg of silver as an aqueous silver ion solution to generate an aqueous silver ammine complex solution. Furthermore, 266 kg of an aqueous 6 wt% aqueous hydrazine solution was added as a reducing agent to this aqueous silver ammine complex solution to obtain a first liquid. The rate of addition of the reducing agent was 80 L / min. The first liquid was in the form of a slurry containing silver particles. Five minutes after the completion of the addition of the reducing agent, 68.8 g of oleic acid (0.1 wt% relative to the weight of silver contained in the silver ammine complex aqueous solution (calculated as 68.8 g oleic acid / 68,800 g silver x 100)) was added as a surface treatment agent. After the addition of the surface treatment agent, the mixture was stirred for five minutes to obtain a second liquid. The second liquid was in the form of a slurry. The second liquid was filtered, washed with water, and then dried to obtain a pre-silver powder. This pre-silver powder is composed of uniform silver particles in an agglomerated state. 16.25 kg of the above pre-silver powder was put into a Henschel type mixer (Mitsui Mining Co., Ltd., FM mixer, model FM75, using SO type stirring blade) and stirred at 900 rpm for 1 minute, after which 37.4 g of oleic acid (0.23 wt% based on the weight of the pre-silver powder (calculated as 37.4 g oleic acid / 16250 g pre-silver powder x 100)) was added as a lubricant and mixed and stirred at a stirring blade speed of 2600 rpm for 20 minutes (lubricant mixing process). This process was carried out in multiple batches to obtain lubricant-treated silver powder in which the lubricant was dispersed on the surfaces of the silver particles. 32 kg of the above lubricant-treated silver powder and 256 kg of SUS balls (diameter 1.6 mm) were put into a vibration mill (manufactured by Chuo Kakoki Co., Ltd., FVR-20 type) and treated for 135 minutes at a vibration frequency of 780 vpm as a flaking treatment, and the lubricant-treated silver powder was flaked to obtain flaked silver powder. After separating the flaked silver powder from the SUS balls, it was stirred for 25 minutes at 2600 rpm in the above Henschel type mixer and crushed. Furthermore, in order to remove coarse particles from the crushed silver powder, it was sieved with a dry sieving device (manufactured by Freund Turbo Co., Ltd., TS125×200 type / 27 μm mesh screen) to obtain flaked silver powder D (crushed silver powder after sieving). Various measurement results of flaked silver powder D are shown in Table 1. FIG. 10 shows an SEM photograph (2000x) of flaky silver powder D.

[0076] (Preparation of flake silver powder E) A 26.28 wt% aqueous ammonia solution (122.1 kg) was added to 2,411 kg of an aqueous silver nitrate solution containing 64.8 kg of silver to generate an aqueous silver ammine complex solution. Further, 6 kg of a 31.15 wt% aqueous sodium hydroxide solution was added to the aqueous silver ammine complex solution, followed by the addition of 158.4 kg of a 37 wt% aqueous formalin solution as a reducing agent. After the addition of the reducing agent was completed, 360 g (0.56 wt. (0.09 wt.% in terms of stearic acid) based on the weight of silver contained in the aqueous silver ammine complex solution) of Cellosol 920 (manufactured by Chukyo Yushi Co., Ltd., containing 15.5 wt.% stearic acid) was added as a surface treatment agent to produce a slurry containing pre-silver powder. The second liquid was filtered, washed with water, and then dried to obtain a pre-silver powder. This pre-silver powder is composed of uniform silver particles in an agglomerated state. 32.2 kg of the pre-silver powder was weighed out and put into a Henschel mixer (Mitsui Mining Co., Ltd., FM mixer, model FM75, using SO-type impeller), and the impeller was rotated at 1200 rpm for 1 minute to disintegrate the mixture. Then, 64.4 g (0.2 wt% based on the weight of the pre-silver powder) of stearic acid was added as a lubricant, and the impeller was rotated at 1200 rpm for 20 minutes. This resulted in a lubricant-treated silver powder in which the lubricant was dispersed on the surfaces of the silver particles. 32 kg of the above lubricated silver powder and 256 kg of SUS balls (diameter 1.6 mm) were put into a vibration mill (Chuo Kakoki Co., Ltd., FVR-20 type) and treated for 60 minutes at a vibration frequency of 1442 vpm as a flaking treatment, and the lubricated silver powder was flaked to obtain flaked silver powder. Furthermore, in order to remove coarse particles, the mixture was sieved using a dry sieving device (Freund Turbo Co., Ltd., TS125×200 type / screen with 27 μm openings) to obtain flaked silver powder E (flaked silver powder after sieving). Table 1 shows the results of various measurements of flaked silver powder E. Figure 11 shows an SEM photograph (2000x) of flaked silver powder E.

[0077] (Preparation of spherical silver powder A) A silver ammine complex aqueous solution was obtained by adding 157.46 g of 28% by mass industrial ammonia water to 3618.2 g of a silver nitrate aqueous solution containing 51.78 g of silver. 9.60 g of a 20% by mass sodium hydroxide aqueous solution was added to this silver ammine complex aqueous solution, and the liquid temperature was adjusted to 25°C. Then, 140.42 g of a 7.3% by mass hydrazine aqueous solution was added as a reducing agent while stirring, to obtain a slurry containing silver particles. To the obtained slurry containing silver particles, 5.93 g of a 3.54 mass % oleic acid ethanol solution was added and stirred. The stirring was stopped to allow the silver particles to settle, and the liquid in which the silver particles had settled was filtered, washed with water until the electrical conductivity of the liquid after passing through the filter was 0.5 mS / m or less, and then dried in a vacuum at 73°C. The silver powder obtained by repeating the above process three times was milled twice for 90 seconds using a sample mill (SK-M10, manufactured by Kyoritsu Riko Co., Ltd.) with 120 g of silver powder charged, to obtain spherical silver powder A. The results of various measurements of spherical silver powder A are shown in Table 1. Figure 12 shows an SEM photograph (2000x) of spherical silver powder A, and Figure 13 shows an SEM photograph (20,000x) of spherical silver powder A.

[0078] (Preparation of spherical silver powder B) 128.2 g of industrial ammonia water with a concentration of 28% by mass was added to 3790.3 g of silver nitrate aqueous solution containing 58.91 g of silver to obtain a silver ammine complex aqueous solution. 9.43 g of nitric acid aqueous solution with a concentration of 80% by mass was added to this silver ammine complex aqueous solution, and further, 0.619 g of polyethyleneimine 600 (PEI600) aqueous solution with a concentration of 5% by mass was added. After adjusting the liquid temperature to 35°C, 338.0 g of hydrazine aqueous solution with a concentration of 2.5% by mass was added as a reducing agent while stirring to obtain a slurry containing silver particles. To the obtained slurry containing silver particles, 4.94 g of a 1.55 mass % stearic acid emulsion solution was added and stirred. The stirring was stopped to allow the silver particles to settle, and the liquid in which the silver particles had settled was filtered, washed with water until the electrical conductivity of the liquid after passing through the filter was 0.5 mS / m or less, and then dried in a vacuum at 73°C. The silver powder obtained by repeating the above process three times was milled twice for 90 seconds in a sample mill (SK-M10, manufactured by Kyoritsu Riko Co., Ltd.) using 120 g of silver powder, to obtain spherical silver powder B. The results of various measurements of spherical silver powder B are shown in Table 1. Also, an SEM photograph (2000x magnification) of spherical silver powder B is shown in Figure 14.

[0079] [Table 1]

[0080] Example 1 Spherical silver powder A corresponding to the first silver powder and flaky silver powder A corresponding to the second silver powder were charged into a Henschel type mixer (FM mixer, model FM75, using SO type stirring blade, manufactured by Mitsui Mining Co., Ltd.) in a mass ratio of 50:50 (first silver powder:second silver powder) to a total weight of 24.8 kg, and mixed and stirred at 900 rpm for 1 minute and at 1500 rpm for 25 minutes. After that, in order to remove coarse particles, the mixture was sieved with a dry sieve device (TS125×200 type / 33 μm mesh screen, manufactured by Freund Turbo Corp.), to obtain a silver powder (mixed silver powder) according to Example 1. Note that the d of flaky silver powder A corresponding to the second silver powder was 1.0 μm. S2 and d of spherical silver powder A corresponding to the first silver powder S1 Difference from (d S2 -d S1The details of the first silver powder and the second silver powder are shown in Table 2. Various measurements were carried out using the silver powder of Example 1. The results are shown in Table 3. In addition, Fig. 2 shows the particle size distribution of the silver powder of Example 1, and Fig. 15 shows an SEM photograph (2000x) of the silver powder of Example 1.

[0081] (Thermal Conductivity) <Formation of evaluation film> 27.9 g of the silver powder according to Example 1 and 2.1 g of the solvent 1-octanol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were charged into a 30 mL plastic pot, and kneading was performed four times for 30 seconds at a revolution speed of 1,400 rpm using a propeller-less self-revolving stirring and defoaming device (manufactured by EME Co., Ltd., V-mini300) to obtain an evaluation film-forming paste (joining metal paste). This evaluation film-forming paste was applied to an alumina substrate using a metal mask with a plate thickness of 50 μm and a squeegee of 10.5 mm x 10.5 mm to form a coating film. The coated alumina substrate was placed in a firing furnace, and an evaluation film was formed by firing without pressure. The pressure-free firing was performed in a nitrogen atmosphere by increasing the temperature to 250°C at 3.75°C / min, and then holding the temperature at 250°C for 1 hour.

[0082] <Measurement of thickness of evaluation film> The average thickness of each of the evaluation films obtained was measured by measuring the step between the non-printed part of the alumina substrate and the part of the evaluation film using a surface roughness meter (Tokyo Seimitsu Co., Ltd., SURFCOM 480B-12).

[0083] <Measurement of thermal conductivity of evaluation film> The volume resistivity of each of the obtained evaluation films was measured at room temperature of 25°C using a four-point probe measuring device (Mitsubishi Chemical Analytech Co., Ltd., Loresta-GX MCP-T700), and the thermal conductivity was calculated from the volume resistivity and temperature using the Wiedemann-Franz law. The results are shown in Table 3. The Wiedemann-Franz law is expressed as the following formula. K / σ=LT (1) In formula (1), K is the thermal conductivity [W / K m], σ is the electrical conductivity [S / m], and L is the Lorentz number (2.44×10 -8 [WΩ / K 2 ]), where T is temperature [K]. Additionally, electrical conductivity σ can be calculated using "1 / ρ", where ρ is volume resistivity [Ω m].

[0084] (Joining strength) <Preparation of bonding layer for evaluation> A copper plate with a size of 10 mm x 10 mm x 1 mm, which was degreased with ethanol and then treated with 10% sulfuric acid, and a Si chip with a size of 2 mm x 2 mm x 0.3 mm with Au on the back electrode were prepared. Next, a metal mask with a thickness of 50 μm was placed on the copper plate, and the above-mentioned bonding metal paste was printed with a size of 2 mm x 2 mm. Next, the Si chip was placed on the bonding material applied to the copper plate, and the thickness between the bonding material and the Si chip was adjusted to 13 μm. Next, the temperature was raised from 25 ° C to 250 ° C at a heating rate of 3.75 ° C / min in a nitrogen atmosphere in a baking furnace, and the main baking was performed by holding at 250 ° C for 60 minutes, and the silver in the silver paste was sintered to form a silver bonding layer, and the Si chip was bonded to the copper plate by this silver bonding layer.

[0085] <Shear strength evaluation> The shear strength of the test piece obtained above was measured using a bond tester SERIES4000Plus (manufactured by Nordson Dage) as shown in FIG. Specifically, the test piece was composed of a copper substrate 3, a silver bonding layer 2 formed thereon, and a Si element 1 formed thereon and bonded to the copper substrate 3 by the silver bonding layer 2. A force was applied from the side of the Si element 1 in the horizontal direction of the copper substrate 3 with a shear tool 4 set at 5 mm / min, and the force at which the Si element 1 broke was divided by the area of ​​the bottom surface of the Si element to determine the shear strength of the test piece, which was taken as the bonding strength of the silver bonding layer. The above test was performed with the lower end of the shear tool 4 abutting at a position 50 μm above the copper substrate 3. The bonding strength was evaluated for representative examples, Example 1, and Comparative Examples 1 and 2 described below. The results are shown in Table 3.

[0086] Example 2 Except for changing the mass ratio of the first silver powder to the second silver powder to 30:70 (first silver powder:second silver powder), a silver powder (mixed silver powder) according to Example 2 was obtained in the same manner as in Example 1. Details of the first silver powder, second silver powder, etc. are shown in Table 2. Various measurements and evaluations were carried out using the silver powder of Example 2. The results are shown in Table 3. In addition, Fig. 3 shows the particle size distribution of the silver powder of Example 2, and Fig. 16 shows an SEM photograph (2000x) of the silver powder of Example 2.

[0087] Example 3 Spherical silver powder A corresponding to the first silver powder and flaky silver powder A corresponding to the second silver powder were mixed and stirred for 1.5 minutes in a sample mill (SK-M10, manufactured by Kyoritsu Riko Co., Ltd.) in a mass ratio of 70:30 (first silver powder:second silver powder) to a total weight of 120 g, and then sieved with a 40 μm mesh to remove coarse particles, thereby obtaining a silver powder (mixed silver powder) according to Example 3. Details of the first silver powder and the second silver powder are shown in Table 2. Various measurements and evaluations were carried out using the silver powder of Example 3. The results are shown in Table 3. In addition, Fig. 4 shows the particle size distribution of the silver powder of Example 3, and Fig. 17 shows an SEM photograph (2000x) of the silver powder of Example 3.

[0088] Example 4 Except for changing the mass ratio of the first silver powder to the second silver powder to 20:80 (first silver powder:second silver powder), a silver powder (mixed silver powder) according to Example 4 was obtained in the same manner as in Example 3. Details of the first silver powder, second silver powder, etc. are shown in Table 2. Various measurements and evaluations were carried out using the silver powder of Example 4. The results are shown in Table 3. In addition, Fig. 5 shows the particle size distribution of the silver powder of Example 4, and Fig. 18 shows an SEM photograph (2000x) of the silver powder of Example 4.

[0089] Example 5 Except for changing the mass ratio of the first silver powder to the second silver powder to 80:20 (first silver powder:second silver powder), a silver powder (mixed silver powder) according to Example 5 was obtained in the same manner as in Example 3. Details of the first silver powder, second silver powder, etc. are shown in Table 2. Various measurements and evaluations were carried out using the silver powder of Example 5. The results are shown in Table 3. In addition, Fig. 6 shows the particle size distribution of the silver powder of Example 5, and Fig. 19 shows an SEM photograph (2000x) of the silver powder of Example 5.

[0090] Comparative Example 1 Various measurements and evaluations were carried out using only the flaky silver powder A. Details of the first silver powder and the second silver powder are shown in Table 2, and the results of the various measurements and evaluations are shown in Table 3. In addition, the particle size distribution of the silver powder according to Comparative Example 1 is shown in FIG.

[0091] Comparative Example 2 Various measurements and evaluations were carried out using only flaky silver powder B. Details of the first silver powder and the second silver powder are shown in Table 2, and the results of the various measurements and evaluations are shown in Table 3. In addition, the particle size distribution of the silver powder according to Comparative Example 2 is shown in FIG.

[0092] Comparative Example 3 Various measurements and evaluations were carried out using only spherical silver powder A. Details of the first silver powder and second silver powder are shown in Table 2, and the results of various measurements and evaluations are shown in Table 3. In addition, the particle size distribution of the silver powder according to Comparative Example 3 is shown in FIG.

[0093] Comparative Example 4 Spherical silver powder A corresponding to the first silver powder and flaky silver powder B corresponding to the second silver powder were mixed and stirred for 40 seconds in a coffee mill (Melitta Japan Co., Ltd., Melitta Electric Coffee Mill ECG-62) in a mass ratio of 20:80 (first silver powder: second silver powder) to a total weight of 50 g, to obtain a silver powder (mixed silver powder) according to Comparative Example 4. The difference (dS2-dS1) between dS2 of flaky silver powder B corresponding to the second silver powder and dS1 of spherical silver powder A corresponding to the first silver powder is 2.2 μm. Details of the first silver powder and the second silver powder are shown in Table 2. Various measurements and evaluations were carried out using the silver powder of Comparative Example 4. The results are shown in Table 3. Fig. 20 shows an SEM photograph (2000x) of the silver powder of Comparative Example 4, and Fig. 27 shows the particle size distribution of the silver powder of Comparative Example 4.

[0094] Comparative Example 5 Spherical silver powder A corresponding to the first silver powder and flake-like silver powder C corresponding to the second silver powder were mixed and stirred for 40 seconds in a coffee mill (Melitta Japan Co., Ltd., Melitta Electric Coffee Mill ECG-62) in a mass ratio of 30:70 (first silver powder: second silver powder) to a total weight of 50 g, to obtain a silver powder (mixed silver powder) according to Comparative Example 5. The difference (dS2-dS1) between dS2 of flake-like silver powder C corresponding to the second silver powder and dS1 of spherical silver powder A corresponding to the first silver powder is 4.2 μm. Details of the first silver powder and the second silver powder are shown in Table 2. Various measurements and evaluations were carried out using the silver powder of Comparative Example 5. The results are shown in Table 3. In addition, Fig. 21 shows an SEM photograph (2000x) of the silver powder of Comparative Example 5, and Fig. 28 shows the particle size distribution of the silver powder of Comparative Example 5.

[0095] Comparative Example 6 Spherical silver powder B corresponding to the first silver powder and flake-like silver powder D corresponding to the second silver powder were mixed and stirred for 1.5 minutes in a sample mill (SK-M10, manufactured by Kyoritsu Riko Co., Ltd.) in a mass ratio of 30:70 (first silver powder:second silver powder) to a total weight of 120 g, and then sieved with a 40 μm mesh to remove coarse particles, to obtain a silver powder (mixed silver powder) according to Comparative Example 6. The difference (dS2-dS1) between dS2 of flake-like silver powder D corresponding to the second silver powder and dS1 of spherical silver powder B corresponding to the first silver powder is 0.0 μm. Details of the first silver powder and the second silver powder are shown in Table 2. Various measurements and evaluations were carried out using the silver powder of Comparative Example 6. The results are shown in Table 3. In addition, Fig. 22 shows an SEM photograph (2000x) of the silver powder of Comparative Example 6, and Fig. 29 shows the particle size distribution of the silver powder of Comparative Example 6.

[0096] Comparative Example 7 Spherical silver powder B corresponding to the first silver powder and flaky silver powder E corresponding to the second silver powder were mixed and stirred for 1.5 minutes in a sample mill (SK-M10, manufactured by Kyoritsu Riko Co., Ltd.) in a mass ratio of 30:70 (first silver powder:second silver powder) to a total weight of 120 g, and then sieved with a 40 μm mesh to remove coarse particles, to obtain a silver powder (mixed silver powder) according to Comparative Example 6. The difference (dS2-dS1) between dS2 of flaky silver powder E corresponding to the second silver powder and dS1 of spherical silver powder B corresponding to the first silver powder is 0.9 μm. Details of the first silver powder and the second silver powder are shown in Table 2. Various measurements and evaluations were carried out using the silver powder of Comparative Example 6. The results are shown in Table 3. In addition, Fig. 23 shows an SEM photograph (2000x) of the silver powder of Comparative Example 7, and Fig. 30 shows the particle size distribution of the silver powder of Comparative Example 7.

[0097] [Table 2]

[0098] [Table 3]

[0099] As is clear from Table 3, the particle size distribution includes a first peak and a second peak, the volume distribution ratio of which is 1% or more, and the particle diameter d M1 and the particle diameter of the second peak d M2 The relationship is represented by the following formula (I) and formula (II): d M1 <d M2 (I) 4.5μm≦d M2 -d M1 ≦16.0μm (II) Fulfilling The relationship between the volume distribution ratio A of the peak having a smaller volume distribution ratio among the first peak and the second peak and the volume distribution ratio B at which the volume distribution ratio between the first peak and the second peak is minimum is expressed by the following formula (III) or formula (IV): 1.2≦A / B (III) 0 = B / A (IV) It is clear that the silver powders (mixed silver powders) of Examples 1 to 5, which satisfy the above, can impart high thermal conductivity to the metal bonding layer.

[0100] As is apparent from Table 3, in a method for producing a mixed silver powder, which includes a mixing step of mixing a first silver powder and a second silver powder, the particle diameter d of the peak of the volume distribution ratio at which the first silver powder is maximized in the particle size distribution of the first silver powder and the second silver powder is 0.01 to 0.01. S1 and the particle diameter d of the peak of the maximum volume distribution ratio of the second silver powder S2 The relationship is expressed by the following formula (i) and formula (ii): d S1 <d S2 (i) 4.6μm≦d S2 -d S1 ≦16.0μm (ii) Fulfilling Cumulative 94% diameter of the first silver powder D 94 and the cumulative 6% diameter D6 of the second silver powder are expressed by the following formula (iii): D 94 <D6···(iii) It can be seen that according to the production methods of Examples 1 to 5 which satisfy the above, it is possible to obtain mixed silver powder capable of imparting high thermal conductivity to the metal bonding layer. [Industrial Applicability]

[0101] According to the present invention, it is possible to provide a mixed silver powder capable of imparting high thermal conductivity to a metal bonding layer, a method for producing the same, and a bonding metal paste containing the mixed silver powder. [Explanation of symbols]

[0102] 1. Silicon element 2 Silver bonding layer 3 Same board 4. Shear Tool

Claims

1. In a particle size distribution measured according to the following procedure, the vertical axis represents the volume distribution ratio (proportion) and the horizontal axis represents the particle diameter, The volume distribution ratio includes a first peak and a second peak, the first peak and the second peak being 1% or more; The particle diameter d of the first peak M1 and the particle diameter d of the second peak M2 The relationship is expressed by the following formula (I) and formula (II): d M1 <d M2 ・・・(I) 4.5μm≦d M2 -d M1 ≦16.0μm・・・(99) Fulfilling The relationship between a volume distribution ratio A of a peak having a smaller volume distribution ratio among the first peak and the second peak and a volume distribution ratio B at which the volume distribution ratio between the first peak and the second peak is minimum is expressed by the following formula (III) or formula (IV): 1.2≦A / B...(III) 0=B / A...(IV) Fulfilling A mixed silver powder having a tap density of 3.5 g / cm 3 or more. (Procedure for measuring particle size distribution) 0.1 g of the mixed silver powder is added to 40 mL of isopropyl alcohol and dispersed for 2 minutes at 19.5 kHz using an ultrasonic homogenizer with a tip diameter of 18 mm, and then the particle size distribution is obtained by wet measurement using a laser diffraction particle size distribution measuring device.

2. In a particle size distribution obtained by measuring according to the following procedure, the vertical axis represents the volume distribution ratio (proportion) and the horizontal axis represents the particle diameter, The volume distribution ratio includes a first peak and a second peak, the first peak and the second peak being 1% or more; The relationship between the particle diameter d M1 of the first peak and the particle diameter d M2 of the second peak is expressed by the following formula (I) and formula (II): dM1 <dM2...(I) 4.5μm≦dM2 -dM1≦16.0μm...(II) Fulfilling The relationship between a volume distribution ratio A of a peak having a smaller volume distribution ratio among the first peak and the second peak and a volume distribution ratio B at which the volume distribution ratio between the first peak and the second peak is minimum is expressed by the following formula (III) or formula (IV): 1.2≦A / B...(III) 0=B / A...(IV) Fulfilling A mixed silver powder, in which more than 50% of the volume distribution ratio of the first peak is derived from spherical silver powder, and more than 50% of the volume distribution ratio of the second peak is derived from flaky silver powder. (Procedure for measuring particle size distribution) 0.1 g of the mixed silver powder is added to 40 mL of isopropyl alcohol and dispersed for 2 minutes at 19.5 kHz using an ultrasonic homogenizer with a tip diameter of 18 mm, and then the particle size distribution is obtained by wet measurement using a laser diffraction particle size distribution measuring device.

3. The above d M1 is 0.5 μm or more and 1.5 μm or less, The above d M2 The mixed silver powder according to claim 1, wherein the average particle size is 5.0 μm or more and 17.5 μm or less.

4. In a particle size distribution obtained by measuring according to the following procedure, the vertical axis represents the volume distribution ratio (proportion) and the horizontal axis represents the particle diameter, The volume distribution ratio includes a first peak and a second peak, the first peak and the second peak being 1% or more; The relationship between the particle diameter d M1 of the first peak and the particle diameter d M2 of the second peak is expressed by the following formula (I) and formula (II): dM1 <dM2...(I) 4.5μm≦dM2 -dM1≦16.0μm...(II) Fulfilling The relationship between a volume distribution ratio A of a peak having a smaller volume distribution ratio among the first peak and the second peak and a volume distribution ratio B at which the volume distribution ratio between the first peak and the second peak is minimum is expressed by the following formula (III) or formula (IV): 1.2≦A / B...(III) 0=B / A...(IV) Fulfilling A mixed silver powder having a ratio of ignition loss to BET specific surface area of ​​0.65 or less. (Procedure for measuring particle size distribution) 0.1 g of the mixed silver powder is added to 40 mL of isopropyl alcohol and dispersed for 2 minutes at 19.5 kHz using an ultrasonic homogenizer with a tip diameter of 18 mm, and then the particle size distribution is obtained by wet measurement using a laser diffraction particle size distribution measuring device.

5. A method for producing a mixed silver powder, comprising a mixing step of mixing a first silver powder and a second silver powder, The first silver powder and the second silver powder were measured by the following procedure, and the particle size distribution was obtained by plotting the volume distribution ratio on the vertical axis and the particle diameter on the horizontal axis. The particle diameter d of the peak of the volume distribution ratio of the first silver powder is maximum S1 and the particle diameter d of the peak of the maximum volume distribution ratio of the second silver powder. S2 The relationship is expressed by the following formula (i) and formula (ii): d S1 <d S2 ・・・(i) 4.6μm≦d S2 -d S1 ≦16.0μm・・・(ii) Fulfilling The cumulative 94% diameter D of the first silver powder 94 and the cumulative 6% diameter D of the second silver powder. 6 The relationship is expressed by the following formula (iii): D 94 ≦D 6 ・・・(iii) A method for producing mixed silver powder that satisfies the above requirements. (Procedure for measuring particle size distribution) 0.1 g of the first silver powder and 0.1 g of the second silver powder are each added to 40 mL of isopropyl alcohol or 40 mL of an isopropyl alcohol solution containing polyvinylpyrrolidone at a concentration of 1 wt %, and dispersed for 2 minutes at 19.5 kHz using an ultrasonic homogenizer with a tip diameter of 18 mm. The particle size distribution is then obtained by wet measurement using a laser diffraction particle size distribution measuring device.

6. The method for producing a mixed silver powder according to claim 5, wherein the first silver powder is a spherical silver powder and the second silver powder is a flake-shaped silver powder.

7. The spherical silver powder has a cumulative 50% diameter D 50 is 0.5 μm or more and 1.5 μm or less, and the tap density is 2.0 g / cm 3 or more, and the BET specific surface area is 0.6 m 2 / g or more 2.2m 2 / g or less, The flaky silver powder has a cumulative 50% diameter D 50 is 5.0 μm or more and 17.5 μm or less, and the tap density is 2.0 g / cm 3 or more, and the BET specific surface area is 0.2 m 2 / g or more 2.0m 2 The method for producing a mixed silver powder according to claim 6, wherein the aspect ratio is 3 or more and the particle size distribution is 1.0 μm / g or less.

8. In a particle size distribution obtained by measuring according to the following procedure, the vertical axis represents the volume distribution ratio (proportion) and the horizontal axis represents the particle diameter, The volume distribution ratio includes a first peak and a second peak, the first peak and the second peak being 1% or more; The relationship between the particle diameter d M1 of the first peak and the particle diameter d M2 of the second peak is expressed by the following formula (I) and formula (II): dM1 <dM2...(I) 4.5μm≦dM2 -dM1≦16.0μm...(II) Fulfilling The relationship between a volume distribution ratio A of a peak having a smaller volume distribution ratio among the first peak and the second peak and a volume distribution ratio B at which the volume distribution ratio between the first peak and the second peak is minimum is expressed by the following formula (III) or formula (IV): 1.2≦A / B...(III) 0=B / A...(IV) A metal paste for joining containing mixed silver powder that satisfies the above requirements. (Procedure for measuring particle size distribution) 0.1 g of the mixed silver powder is added to 40 mL of isopropyl alcohol and dispersed for 2 minutes at 19.5 kHz using an ultrasonic homogenizer with a tip diameter of 18 mm, and then the particle size distribution is obtained by wet measurement using a laser diffraction particle size distribution measuring device.

Citation Information

Patent Citations

  • Silver powder for silver clay and silver clay containing the silver powder

    JP2006118042A

  • Metal paste for bonding

    JP2014224296A

  • Silver powder and method for producing the same

    JP2021006661A

  • CONDUCTIVE PASTE, LAMINATE AND METHOD FOR BONDING Cu SUBSTRATE OR Cu ELECTRODE AND CONDUCTOR

    JP2022006413A

  • Method for producing sintered compact

    JP2024051765A